Israel and the diaspora: problems of cognitive dissonance - Safran, W (International Migration Institute, 2012)
The relationship between Israel and the diaspora has been marked by mutual accommodation. The diaspora has come to accept the fact that Israel is not exempt from the problems and pathologies of states and societies; and Israel has acknowledged the continuation of the diaspora as a centre of Jewish life. Both sides are subject to illusions. Jews in the diaspora believe that Israel will be better supported by their hostland’s political right rather than its left; that Israel can be saved, despite itself, by a kind of 'tough love’ bestowed upon it by the diaspora or its hostland governments; and that Jewish identity and survival, based on an autonomous and largely secular culture, can be assured regardless of whether Israel exists or not. Israel’s illusions are that it can be 'like other nations’; that it can replicate in short order the civic nations that France and the United States became after many generations; and that it must 'de-ethnicise’ and de-Judaise to become acceptable to its neighbours.